MEDIA GEOGEBRA DALAM PEMBELAJARAN MATEMATIKA - Japa, Ngurah; Suarjana, I Made; Widiana, Wayan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The aims of research are : (1) for knowing the differences in the result of geometry learning between the student that follow realistic mathematic education by media geogebra and the student that follow conventional learning, (2) The interaction between realistic mathematic education by media geogebra with spatial ability related geometry learning, (3) The differences in the result result of geometry learning between the student that follow realistic mathematic education by media geogebra and the student that follow conventional learning in the group of student have the high of spatial ability, (4) The differences in the result of geometry learning between the student that follow realistic mathematic education by media geogebra and the student that follow conventional learning in the group of student have the low of spatial ability. The research in SMP N 2 Kuta Utara with the sample of the population amounted to 110 eighth of all students in grade VIII in learning year of 2013/2014 is as many as 330 students. The type of research is ouasi eksperiments. Before taking samples ANOVA test equality with one way. As for the data analysis carried out tests of normality and homogeneity of variance test. And then the date of spatial and the research of geometry learning with use by descriptive statistic and Anava with two way. Based on the result of analysis found the result as following : (1) Have the differences in the result of geometry learning between the the student that follow realistic mathematic education by media geogebra and the student that follow conventional learning by grade VIII at SMP N 2 Kuta Utara, (2) Have interaction realistic mathematic education by media geogebra with spatial ability for the result of geometry learning in grade VIII SMP N 2 Kuta Utara (F = 5,937 (p < 0,05), (3) Have the significant difference on the result of geometry learning between the student that follow realistic mathematic education by media geogebra and the student that follow conventional learning in the group of student have the high of spatial ability in SMP N 2 Kuta Utara, (4) Have the significant difference on the result of geometry learning between the student that follow realistic mathematic education by media geogebra and the student that follow conventional learning in the group of student have the low of spatial ability in SMP N 2 Kuta Utara.